How do work characteristics affect job performance? An investigation in Vietnam - Pham Thu Trang (Cogent Business & Management, 2022)
This study aims to examine how work characteristics influence employee performance through the mediating role of job-based psychological ownership in a developing country. The research employed 432 Vietnamese employees from 10 manufactories located in three regions of Vietnam: The North, the Middle and the South of Vietnam. The results reveal that job-based psychological ownership mediates four relationships between task identity, task significance, autonomy, feedback, and in-role performance. Unexpectedly, skill variety, the remaining work characteristic considered here, does not impact job-based psychological ownership, meaning that here the mediating role of job-based psychological ownership does not exist. This paper concludes with discussions and recommendations for Vietnamese businesses.
Keywords: 650; developing economy; human capital; in-role performance; job-based psychological ownership; structural equation modeling; work characteristics